Financial Bubbles in Interbank Lending - Luisa Corrado; Tobias Schuler (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
As a result of the global financial crisis countercyclical capital requirements have been discussed to prevent financial bubbles generated in the banking sector and to mitigate the adverse effects of financial repression after a bubble burst. This paper analyses the effects of an endogenous capital requirement based on the credit-to-GDP gap along with other policy instruments. We develop a macroeconomic framework which endogenizes market expectations on asset values and allows for interbank transactions. We then show how a bubble in the banking sector relaxes financing constraints. In policy experiments we find that an endogenous capital requirement can effectively reduce the impact of a financial bubble. We show that central bank intervention (against the wind") instead has only a minor effect.
Keywords: E44; E52; 330; Financial bubbles; credit-to-GDP gap; endogenous capital requirement; stabilization policies